ΑΝ EXAMPLE OF GEOGRAPHICAL INFORMATION SYSTEMS (GIS) AND ARTIFICIAL INTELLIGENCE SYSTEMS (FUZZY LOGIC & NEURAL NETWORKS) CONJUNCTION: APPLICATION IN GEOMORPHOLOGY - ΓΚΟΥΡΝΕΛΟΣ, Θ.; ΕΥΕΛΠΙΔΟΥ, Ν.; ΒΑΣΙΛΟΠΟΥΛΟΣ, Α. (Bulletin of the Geological Society of Greece, 2005)
In this paper we are studying the erosional procedures on the basis of Geographical Information Systems (GIS) and Artificial Intelligence (Al) methods. More precisely we use fuzzy logic rules to estimate the erosion risk index for the surface rocks and a model of neural networks to spatially categorise the erosion risk index. The described procedure is applied at Zakynthos island, where a complete spatial database already exists.